Can Aspirin Use Be Associated With the Risk or Prognosis of Bladder Cancer? A Case-Control Study and Meta-analytic Assessment - Fan, Bo; Mohammed, Alradhi; Huang, Yuanbin; Luo, Hong; Zhang, Hongxian; Tao, Shenghua; Xu, Weijiao; Liu, Qian; He, Tao; Jin, Huidan; Sun, Mengfan; Sun, Man; et al. (Frontiers in Oncology, 2021)
Aspirin, widely used to prevent cardiovascular disease, had been linked to the incidence of bladder cancer (BCa). Existing studies focusing on Chinese populations are relatively rare, especially for Northeast China. Meanwhile, relevant studies on the effects of aspirin on the occurrence or prognosis of BCa are inconsistent or even controversial. First, in the case control study, logistic regression analysis was used to investigate the association between aspirin intake and risk of BCa including 1121 patients with BCa and the 2242 controls. Subsequently, Kaplan-Meier curve and Cox regression analyses were applied to explore the association between aspirin intake and cliniopathological factors. Finally, we quantificationally combined the results with those from the published literature evaluating aspirin intake and its effects on the occurrence, outcome of surgery and prognosis of BCa. Our case-control study demonstrated that the regular use of aspirin was not associated with a reduced incidence of BCa (P=0.175). Stratified analyses of sex showed that aspirin intake did not lead to a lower risk of BCa in in female patients (P=0.063). However, the male population who regularly took aspirin had a lower incidence of BCa (OR=0.748, 95% CI= 0.584-0.958, P=0.021). Subgroup analyses stratified by smoking found a significant reduction in the risk of BCa in current smokers with aspirin intake (OR=0.522, 95% CI=0.342-0.797, P=0.002). In terms of prognosis of BCa, patients with a history of aspirin intake did not had a markedly longer overall survival or recurrence-free survival than those with no history of aspirin intake by Kaplan-Meier curves. However, in people younger than 68, aspirin intake seemed to have prolonged effects for overall survival (HR=3.876; 95% CI=1.326-11.325, P=0.019). Then, we performed a meta-analysis involving 39527 BCa cases and found that aspirin intake was not associated with the occurrence of BCa (P=0.586). Subgroup analysis by whether regular use of aspirin, by the mean duration of use of aspirin, by sex, by smoking exposure, by research region and by study type also supported the above results. Moreover, the combined results involving 8825 BCa cases showed that patients with aspirin intake did not have significantly influence on prognosis of patients.